2011
DOI: 10.1002/pd.2678
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of congenital vascular rings and slings: sonographic features and perinatal outcome in 81 consecutive cases

Abstract: Congenital vascular rings can be diagnosed with prenatal ultrasound using the three-vessel trachea view and subsequent fetal echocardiography with particular attention to the relationship of the aortic arches, ductal arches, and the trachea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 13 publications
2
54
1
Order By: Relevance
“…As cardiologists have become more facile with the technology, echocardiography has become a more widely used screening test to identify intrathoracic aberrant vasculature that may cause tracheal compression and stridor without exposing the child to radiation. 31 …”
Section: Ida and Thompsonmentioning
confidence: 97%
“…As cardiologists have become more facile with the technology, echocardiography has become a more widely used screening test to identify intrathoracic aberrant vasculature that may cause tracheal compression and stridor without exposing the child to radiation. 31 …”
Section: Ida and Thompsonmentioning
confidence: 97%
“…7 However, current fetal series report a VR incidence of 1 to 1.5:1000. [3][4][5][6] The conflicting The development of multidetector computed tomography has triggered a revolution in the study of the aorta and other large vessels and has replaced angiography in the diagnosis of congenital anomalies of the aortic arch, particularly vascular rings. The major advantage of multidetector computed tomography is that it permits clear 3-dimensional assessment of not only vascular structures, but also airway and esophageal compression.…”
Section: Introductionmentioning
confidence: 99%
“…However, these structures are currently often diagnosed in the prenatal period and are asymptomatic in both the neonatal period and later years. [3][4][5][6] The most frequent VR are the double aortic arch (DAA) and the right arch with aberrant left subclavian artery (ALSA). In the DAA, the left and right aortic arches themselves compress the airway and esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Another two had mild symptoms, which improved. Computed tomographic angiography and barium swallow at 2 and 5 years of age showed no significant obstruction Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Chaoui (2002) 25 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Current study Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Bronshtein (1998) 6 Gul (2012) 29 Miranda (2014) 28 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Chaoui (2002) 25 Gul (2012) …”
Section: Cohort Studymentioning
confidence: 99%
“…Almost all studies showed an overall good rate with regard to the selection and comparability of the study groups and for the ascertainment of the outcome of interest. The main weaknesses of these studies were their small sample size, being series from high-risk populations, Bronshtein (1998) 6 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) Bronshtein (1998) 6 Patel (2006) 10 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Miranda (2014) 28 Razon ( Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Miranda (2014) 28 Razon (2014) and lack of ascertainment of all individual outcomes. Furthermore, most studies had a relatively short period of follow-up after birth.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%